FEATURES OF THE FORMATION MODEL OF PROFESSIONAL COMPETENCE OF FUTURE LAND USE SPECIALISTS - Dankeeva, O. (Continuing Professional Education: Theory and Practice, 2019)
This article uncovers main notions, principles and approaches that are necessary for the formation of professional competence of future land use professionals. The structure, conditions for the realization of a model and its content were reviewed. The structural components of a professional competence were suggested to be such: subject’s direction in the field and mastered technical skills, ability to integrate with the experience, such as ability to correlate ones activity with the already acquired practices of land use field, ability to effectively interact with colleague’s experience and innovations as well as an ability to generalize and relay your own experience to others. In the course of studying the features of the model we have analysed approaches to the modeling of processes that were distinguished in the pedagogical science. It proved our beliefs that the main goal of assembling the model of professional competence of future land use planning specialists is to ensure efficiency and mobility of the system using various methods as well as ensure its ability to quickly adapt to changing conditions